Teatro in immagine. Sguardi, ambienti, dispositivi - Rimini, Stefania (Scenari, 2021)
Theatre is the natural cradle of opsis – a term which indicates the invention of a unique visual perspective capable of taking the relationship between subject and representation to its extremes. Whilst dependant on spoken language as its primary element, Western dramaturgy has been swept by a visual vertigo which brought about the “theatre of images”. Owing to the impact of Visual culture, we can now reassess certain dramaturgical practices and theatre techniques in a more fluid, dynamic perspective – one which will do justice to concepts such as “gaze”, “environment” and “device”. The following essay aims to draw a preliminary map of theoretical and methodological perspectives on the relation between theatre and visual context through the dissection of two case studies: Giovanni Testori’s “eye theory” and the tribute to Pasolini’s Petrolio by Motus.